Aktivitas Siswa Mengikuti Kegiatan Mentoring Hubungannya Dengan Karakter Disiplin Di Sekolah - Fajar Farham Hikam; Agustiani Sri Rahayu (Journal of Cross Knowledge, 2023)
Student Activities Participating in Mentoring Activities Relates to Their Disciplinary Character at School, (Correlational Research at Madrasah Aliyah Mambaul'ulum Cianjur) This research is motivated by the low quality of student discipline at Madrasah Aliyah Mambaul'ulum Cianjur, the causal factor is a lack of awareness of feelings. students' responsibility to obey school rules and regulations. Based on preliminary studies, information was obtained that there were many students who violated school rules, especially regarding inappropriate arrival times to school, and student behavior/actions in learning activities. The aim of this research is to find out: (1) The reality of students' activities taking part in mentoring activities; (2) The reality of the character of discipline; (3) The relationship between students' activities taking part in mentoring activities and the disciplinary character at the Madrasah Aliyah Mambaul'ulum Cianjur school. The method used in this research is the correlation method. The approach method used is quantitative. This method is used to compare the measurement results of two different variables in order to determine the relationship between the two variables. The data collection techniques used were questionnaire techniques, observation, interviews and documentation.